PEMBUATAN DAN KARAKTERISASI PELET IKAN DARI BULU AYAM - Syamsul Huda; Sulhadi Sulhadi; Mahardika Prasetya Aji (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Quill is a waste of chicken slaughterhouse with a plentiful amount and increase with the chicken population and the level of cuts as a result of increased demand for chicken meat in the market. Nowadays, it has not been widely used, and only a small fraction is used as an ingredient to make a feather duster, seat fillers, fertilizer plants, crafts / ornaments and shuttle cock (Adiati et al., 2004). This study aims to provide characterization of the fish pellet feed material from chicken feathers by physically tested. The physical test done by resistance to water, porosity, and the buoyancy test. The results of analysis of test score results physically namely durability against water fish pellets is 18.6 minutes, the degree of porosity of 64.25%, and the buoyancy by 46.25 minutes. Chicken feathers can be used as an alternative to fish pellet feed material.Keywords: Pellets of fish, Chicken feathers, A physical test.